Molecular Medicine 2019
DOI: 10.5772/intechopen.88563
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics: Basic Principles and Strategies

Abstract: Metabolomics is the study of metabolome within cells, biofluids, tissues, or organisms to comprehensively identify and quantify all endogenous and exogenous low-molecular-weight (<1 kDa) small molecules/metabolites in a biological system in a high-throughput manner. Metabolomics has several applications in health and disease including precision/personalized medicine, single cell, epidemiologic population studies, metabolic phenotyping, and metabolome-wide association studies (MWAS), precision metabolomics, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…Of the three fields, genomics has been the most utilized for clinical virology purposes; however, there is significant interest in leveraging alternative approaches such as metabolomics and proteomics to address remaining gaps. Metabolomics, or the large-scale study of small molecules, represents a change in paradigm from routine clinical virology diagnostics as it detects host metabolic response rather than directly detecting the pathogen [17] . Metabolomics theoretically holds promise for infectious diseases applications as it can be performed directly from patient specimens from minimal sample volume, is inexpensive to run, provides a real-time assessment of host response and may accurately differentiate active infection from colonization [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the three fields, genomics has been the most utilized for clinical virology purposes; however, there is significant interest in leveraging alternative approaches such as metabolomics and proteomics to address remaining gaps. Metabolomics, or the large-scale study of small molecules, represents a change in paradigm from routine clinical virology diagnostics as it detects host metabolic response rather than directly detecting the pathogen [17] . Metabolomics theoretically holds promise for infectious diseases applications as it can be performed directly from patient specimens from minimal sample volume, is inexpensive to run, provides a real-time assessment of host response and may accurately differentiate active infection from colonization [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites are small molecules (<1000 Da) that play a crucial role in managing pathways in any organism. 36 They include nucleotides, nucleosides, amino acids, glucose moieties, and more. Metabolites work at all the levels of central dogma to manage interrelated pathways meticulously.…”
Section: Omics-based Technology Platform For Covid-19 Researchmentioning
confidence: 99%
“…79 The metabolome is defined as the set of metabolites present in a given biological system, fluid, cell, or tissue at a given time. 80 The topological connections among these molecules define the groups, and the characteristic displays how the system evolves concerning metabolic fluxes and environmental stimuli. 81 Numerous metabolomics studies confirmed an attempt to define higher the pathways altered in schizophrenia and its therapeutics.…”
Section: Metabolic Biomarkersmentioning
confidence: 99%